Application of Virtual Map of Campus Building STMIK Jakarta STI & K using Macromedia FlashMX Professional 2004 - Aryo Budisatrio (Jurnal Manajemen Informatika, 2010)
The development of computerized technology in the current growing popularity with the internet oninformation technology. Through the internet facility is much information can be found in various formsof both images and text.Through this internet technology STMIK Jakarta STI & K can provide more information about facilitiesand other information. One of them is information on facilities located on campus buildings STMIK STI &K. Jakarta